Comparison of efficacy and safety of accelerated trans-epithelial crosslinking for keratoconus patients with corneas thicker and thinner than 380μm. (3rd April 2022) - Abe, Kentaro; Miyai, Takashi; Toyono, Tetsuya; Aixinjueluo, Wei; Inoue, Tatsuya; Asano, Shotaro; Ishii, Hitoha; Yoshida, Junko; Shirakawa, Rika; Usui, Tomohiko
ABSTRACT: Purpose: Accelerated trans-epithelial cross-linking (ATE-CXL), a therapy to halt keratoconus progression, has the merit of widening the indications for thinner corneas (<380 μm). Since a hypotonic solution affects the swollen cornea, corneas of <380 μm thickness at preoperative measurement can be an indication for ATE-CXL. The aim of this retrospective study was to compare the efficacy and safety of ATE-CXL for keratoconus between corneas with thicknesses <380 μm and ≥380 μm. Materials and Methods: Thirty-four eyes of 27 patients who underwent ATE-CXL (30 mW/cm 2 ; 3 minutes) with completion of a 24-month follow-up, were enrolled and divided into two groups: Group 1, thinnest corneal thickness (TCT), <380 μm (n = 10) and Group 2, TCT, ≥380 μm (n = 24). A hypotonic solution was administered to Group 1 until the corneal thickness increased by >380 μm before UV-A irradiation. We measured uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), maximum and average keratometric values (Kmax and AveK), central corneal thickness (CCT), TCT by anterior segment optical coherence tomography, and corneal endothelial cell density (ECD) using specular microscopy. The changes from baseline to 24 months postoperatively between the two groups were compared accordingly. Results: The changes in Kmax and AveK from baseline to 24 months in Group 1 (ΔKmax: −7.8 ± 7.7 D, ΔAveK: −4.3 ± 6.1 D) showed significant decreases compared to those in Group 2 (ΔKmax: 0.2 ± 3.0 D, ΔAveK: 0.6 ± 2.7 D) ( p = .004 and p = .001), and there were no significant changes from baseline to 24 months postoperatively in UCVA, BCVA, CCT, TCT, and ECD in both groups. Conclusion: ATE-CXL is effective and safe for keratoconic corneas in both groups. The effect of reducing keratometric values was greater in the group with thinner corneas.